Writing research papers : investigating resources in cyberspace - Woodward, Jeannette A. (Lincolnwood, Illinois USA : NTC/Contemporary Publishing Group, 1999)
Offers advice on how to research a paper using the latest information available on the Internet.
Includes bibliographical references and index.
Young Adult.
Young Adult
Keywords: Internet in education; Internet; Report writing -- Data processing